Stress Coping Mechanism by the Restaurateurs of Bangalore City - M. , Nimisha; Dharmaraj, Arumugam (International Journal of Psychosocial Rehabilitation, 2020)
Entrepreneurship is a pioneering venture that is exigent and so, it is stressful. Restaurateurs indulge in ventures that deal with highly perishable food stuff that requires swift vending. It is also important to understand and provide valuable suggestions on how to cope with stress. The objective of the study is to understand the stress faced by the restaurateurs and their coping mechanism. The reviewed literature shows the potential issues that are concerned with stress undergone by the entrepreneurs. There is a scarcity of research with respect to the management of stress with respect to the restaurateurs of Bangalore city. People who manage the restaurants are called restaurateurs. A total number of 100 restaurateurs were taken as a sample size for the study. Analysis of the data was done using the primary data collected through questionnaires from the restaurateurs of Bangalore city.